2014
DOI: 10.3168/jds.2013-7731
|View full text |Cite
|
Sign up to set email alerts
|

Within-milking variation in milk composition and fatty acid profile of Holstein dairy cows

Abstract: Changes in milk composition during a milking are well characterized, but variation in milk fatty acid (FA) profile is not well described and may affect the accuracy of in-line milk composition analyzers and could potentially be used for selective segregation of milk. Within-milking samples were collected from 8 multiparous high-producing Holstein cows (54.86 ± 6.8 kg of milk/d; mean ± standard deviation). A milk-sampling device was designed to allow collection of multiple samples during a milking without loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
4
11
2
Order By: Relevance
“…Thus, the absence of the effect of milking time on the butterfat content of vaccenic acid was reflected in a similar content of rumenic acid, although the activity of the SCD enzyme was 14% higher (P<0.001) in the butter produced from milk from the cows that were milked in the afternoon (Table 5). In contrast to the present study, higher concentrations of rumenic and vaccenic acids were obtained in milk from the cows that were milked during the P.M. milking session (FERLAY et al, 2010;RICO et al, 2014;SCHWENDEL et al, 2015;VIBART et al, 2017).…”
Section: Indexcontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, the absence of the effect of milking time on the butterfat content of vaccenic acid was reflected in a similar content of rumenic acid, although the activity of the SCD enzyme was 14% higher (P<0.001) in the butter produced from milk from the cows that were milked in the afternoon (Table 5). In contrast to the present study, higher concentrations of rumenic and vaccenic acids were obtained in milk from the cows that were milked during the P.M. milking session (FERLAY et al, 2010;RICO et al, 2014;SCHWENDEL et al, 2015;VIBART et al, 2017).…”
Section: Indexcontrasting
confidence: 99%
“…These results corroborate the literature regarding the higher concentration of oleic acid and the lower palmitic acid in milk from cows milked during the P.M. milking (FERLAY et al, 2010;RICO et al, 2014;SCHWENDEL et al, 2015). Some of these results can be explained by the higher (P<0.001) SCD enzyme activity for the pairs oleic/ stearic and palmitoleic/palmitic acids (Table 5).…”
Section: Indexsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent reports (Winterholler et al, 2012;Gunn et al, 2014) have indicated that milk fat in beef cows may be as low as 1.4% to 1.7%, however, it is possible that milk fat values in the present experiment were considerably lesser than expected because of incomplete emptying of the quarter at sampling. Nevertheless, it has been reported that within milking variation in milk components and fatty acids is low to none (Larsen et al, 2012;Rico et al, 2014). Milk lactose decreased from day 68 to 116 (day effect; P < 0.001) and milk solids increased from day 68 to 116 (day effect; P < 0.001) for both treatments.…”
Section: Milkmentioning
confidence: 92%
“…Soyeurt et al (2006), Rutten et al (2009) and Soyeurt et al (2011) presented results for predicting single FA and groups of different FA with MIR in the wavenumber range 1000 to 5000/cm. Rico et al (2014) took several subsamples during the milking process, analysed them in laboratory, and evaluated within milking fatty acids profiles during the milking process. The subsamples showed increased concentrations of short chain fatty acids (SCFA) during the main part of milking and less LCFA at the end of milking (Rico et al 2014).…”
mentioning
confidence: 99%